Utilization of Google Colaboratory to Determine the Relationship Between the National Defense Index (IBNU) and the Human Development Index (HDI) in Indonesia in 2023 - Rifai, Bachtiar; Poniman, Aris; Gultom, Rudy Agus Gemilang; Wadjdi, Achmad Farid; Rifai, Salsabila Azzahra (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
This study uses Random Forest model and statistical analysis to evaluate the relationship between the Index of State Defense (IBNu) and the Human Development Index (HDI) at the provincial level in Indonesia. The data includes the average IBNu, HDI in 2023, the manager's prediction, and data from the Indonesian Democracy Index (IDI) in 2021-2023. The model shows excellent prediction performance with a Mean Squared Error (MSE) of 0.0018 and an R² value of 0.97, indicating that the prediction results are very close to the actual data. The residual plot also shows that the model has no significant bias as the prediction error is evenly distributed around the zero line. Correlation analysis found that HDI has a strong positive correlation with education variables, such as Expected Years of Schooling and Average Years of Schooling, while IBNu is negatively correlated with economic growth, indicating that an increase in IBNu may have the effect of decreasing economic growth. The classification performance of the model was assessed using the confusion matrix, which showed accuracy, precision, recall, and F1 scores of 0.8, indicating the model's ability to distinguish between the various classes well. These results suggest that IBNu policies aimed at improving HDI may not always be effective and that a more comprehensive policy approach is needed. The proposed recommendations include the integration of national defense and human development programs into the school curriculum, balanced budget allocation, innovative programs for the community, support for the balance between security and welfare, and continuous research and evaluation.